2006
DOI: 10.1021/jf061002r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Deamidation on the Structure, Surface Hydrophobicity, and Emulsifying Properties of the Z19 α-Zein

Abstract: Different deamidation conditions for the Z19 alpha-zein were studied in order to find the best conditions for the development of the emulsifying properties. Alkaline deamidation was chosen, and the effects on the peptide bond cleavage, secondary structure, emulsifying properties, and surface hydrophobicity were studied. The Z19 alpha-zein was deamidated by using 0.5 N NaOH containing 70% ethanol at 70 degrees C for 12 h. A deamidation degree (DD) of 60.6 +/- 0.5%, and a degree of hydrolysis (DH) of 5 +/- 0.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 42 publications
4
74
0
2
Order By: Relevance
“…However, such phenomenon was not found in our zein samples, indicating that zein retained its primary structure upon the mild pH treatment. Although FTIR and zeta-potential results showed that zein underwent deamidation, especially at the conditions of pH 2.7 and pH 12.5, the band pattern of protein electrophoresis for monomer and dimer zein indicated that the deamidation of glutamine did not change the zein molecular weight, which agreed with the results of alkaline deamidated zein by Cabra et al (2007). Besides, no increase in molecular weight was observed as well, which indicates that no polymerisation of zein molecules occurred in mild pH solutions.…”
Section: Sds-page Analysissupporting
confidence: 71%
See 4 more Smart Citations
“…However, such phenomenon was not found in our zein samples, indicating that zein retained its primary structure upon the mild pH treatment. Although FTIR and zeta-potential results showed that zein underwent deamidation, especially at the conditions of pH 2.7 and pH 12.5, the band pattern of protein electrophoresis for monomer and dimer zein indicated that the deamidation of glutamine did not change the zein molecular weight, which agreed with the results of alkaline deamidated zein by Cabra et al (2007). Besides, no increase in molecular weight was observed as well, which indicates that no polymerisation of zein molecules occurred in mild pH solutions.…”
Section: Sds-page Analysissupporting
confidence: 71%
“…Therefore, zein finds many potential applications in food and pharmaceutical industries including but not limited to tablet coating and free-standing packaging materials (Hernandez-Izquierdo & Krochta, 2008), emulsifier (Cabra, Arreguin, Vazquez-Duhalt, & Farres, 2007;Casella & Whitaker, 1990;Yong, Yamaguchi, Gu, Mori, & Matsumura, 2004), chewing-gum base (Liu & Lee, 2004), antioxidant (Chiue, Iwami, Kusano, & Ibuki, 1994;Zhu, Chen, Tang, & Xiong, 2008), drug encapsulant (Guo & Shi, 2009;Hurtado-Lopez & Murdan, 2005;Liu, Sun, Wang, Zhang, & Wang, 2005;Zhong & Jin, 2009), and tissue scaffold (Gong, Wang, Sun, Xue, & Wang, 2006;Tu et al, 2009;Wang et al, 2007. Many of these applications (e.g., chewinggum base and antioxidant) are counting on zein's native property, which is high in aliphatic indexes and surface hydrophobicity (Argos et al, 1982;Cabra et al, 2007) and high in fatty acid-binding capacity (Chiue, Kusano, & Iwami, 1997). Whereas, for other applications (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations